ANALISIS LAJU PERGERAKAN HARGA SAHAM EMITEN INDUSTRI PERTAMBANGAN BERDASARKAN PADA CAPAIAN PROFIT, IHSG DAN BUNGA PENJAMINAN - noerchoidah, noerchoidah; Harryono, Sumadji (Majalah Ekonomi, 2018)
Before investing in stocks, individual or organization must ensure that the investment made is correct. This can performed by applying a variety of alternative methods for valuing whether Preferred stock is really a stock that will bring positive returns in the future. One alternative investment appraisal is based on analysis of fundamental or company performance. Profitability ratios demonstrate the ability company in making a profit is one way to know the performance of the company. This study aimed to know whether there is influence profitability ratios - as one corporate performance indicators - the stock price. The object in this study were sixteen companies engaged in the mining industry that are listed on the Indonesian Stock Exchange. Understanding the empirical description of stock prices movement on the economical setting, firm’s perform, and the behavior of its IHSG. This study evaluates the effect of three factors: firm’s profitability, interest rate, and IHSG, toward the stock prices movement of 16 mining and mining service stocks listing at Indonesian Stock Exchange (BEI). This analysis indicated that the stock prices movement was the most dominant influenced by IHSG followed by interest rate (negative) and firm’s profitability. This study also found that IHSG would become an effective intervening variable for transmitting both ROI and interest effect toward the stock prices movements, and hence the role of IHSG could be adopted as investor strategy